Effect of chemical treatment of pineapple crown fiber in the production, chemical composition, crystalline structure, thermal stability and thermal degradation kinetic properties of cellulosic materials - Pereira, Paulo Henrique Fernandes [UNESP]; Ornaghi, Heitor Luiz [UNESP]; Arantes, Valdeir; Cioffi, Maria Odila Hilário [UNESP] (Elsevier, 2021)
Recently, the growing environmental concerns and economic demands have driven the need to develop effective solutions for the treatment of vegetal fibers to be used as renewable source for various industrial applications. The present study aimed to explore pineapple crown fibers (PCs) as an alternative source of cellulose. The three treatments (alcohol-insoluble residue (AIR), alkaline (AT), and organosolv) evaluated promoted chemical and morphological changes to the PCs. Fresh and treated PCs were characterized by Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Scanning electron microscopy (SEM), thermogravimetric analysis (TG), and chemical composition. The XRD results showed that the Cellulose-I allomorph was not altered during extraction, and that the crystallinity index of the fibers treated with AT, first bleaching step, second bleaching step, and the second bleaching step followed by KOH treatment (2B_KOH) increased to 77.8; 83.2; 83.5 and 86% when compared with fresh PC (62.3%). Results from the thermal analysis revealed that thermal stability increased for the isolated cellulose, and the maximum degradation for (2B_KOH) is 350 °C. Chemical composition results showed a decrease in the content of hemicellulose, lignin and other soluble materials after alkaline treatment, suggesting high-quality 2B_KOH with 74.6% of cellulose. SEM revealed changes in the morphological structure on fibers. Alkaline treatment followed by H2O2 bleaching is an excellent alternative for the removal of non-cellulosic material and facilitates the isolation of cellulose. These results suggested that there is a potential to isolate cellulose from PC via the sequence of treatment of a methodology by chlorite-free.
Keywords: Chemical treatment; Lignocellulosic fiber; Pineapple crown's fibers; Potassium hydroxide; Thermal degradation kinetic